The crystal structure of diaqua-bis(pyrazolo[1,5-a]pyrimidine-3-carboxylato-κ2N,O)manganese(II), C14H12N6O6Mn - Hong Dong-Feng; Li Meng-Fei; Chu Tian-Tian (Zeitschrift für Kristallographie - New Crystal Structures)
C14H12N6O6Mn, monoclinic, P21/n (no. 14), a = 7.0839(3) Å, b = 13.1211(4) Å, c = 8.9854(3) Å, β = 112.359(5)∘, V = 772.39(5) Å3, Z = 2, Rgt(F) = 0.0274, wRref(F2) = 0.0725, T = 293 K.